Pengeruh Lingkungan Belajar Terhadap Minat Belajar Siswa Pada Mata Pelajaran Tahfiz Qur’an Di SMP Muhhammadiyah 8 Medan - Pepayosa, Emia; Zuliana, Zuliana (Al-Ulum: Jurnal Pendidikan Islam, 2024)
The Al-Qur'an is the sentence of Allah SWT which was revealed to the Prophet Muhammad saw, which must be believed, applied and practiced in everyday life. It is written in the Arabic mushaf, which has been handed down to us through mutawatir history, that memorizing the Al-Qur'an contains worship, but current symptoms show that some individuals consider memorizing the Al-Qur'an to be just a formality and some even forget. The emergence of these symptoms has several factors, one of which is the environment. The aim of this research is to determine the influence of the learning environment on students' interest in learning in the Tahfiz Qur'an subject at SMP Muhammadiyah 8 Medan, this type of research is quantitative. This research is a population study of 60 students, and a sample of 20 students specifically in class VII (C) in the Tahfiz Qur'an subject at SMP Muhammadiyah 8 Medan. The benefit of this research is to find out whether student interest is influenced by the learning environment. This research uses a quantitative correlational method, because this method aims to find out whether the independent variable is influenced by the dependent variable. This data collection technique is by distributing questionnaires, then the data will be managed through the SPSS application with the Case Processing Summary test, One-Sample Test, Overall Agreement, which states that the X and Y values are 0.05. So it can be concluded that the influence of the environment is correlated with the learning interest of class VII (C) students in the Tahfiz subject at SMP Muhammadiyah 8 Medan.